Coffee Ground: The Economic and Perfect Wound Dressing - Yuwono, Hendro Sudjono; Noor, Ismet M.; Masria, Sadeli (British Journal of Healthcare and Medical Research, 2022)
The coffee ground has inherent an antioxidant, anti-inflammatory, and antimicrobial, creating the best dressing for acute and chronic wounds. It may find a cost-effective, simple procedure, and different from the wound dressing known today. Coffee powder for damages has the understanding to save the growth of the wound cells. We remained a thin coffee layer for keeping the wound bed cells safe and faster healing process. Protecting the wound bed cells promotes economic dressing and perfect healing.